Acteurs de la communication des entreprises et organisations : pratiques et perspectives - Sophie Del Fa (Communiquer)
This work “Acteurs de la communication des entreprises et organisations: pratiques et perspectives”, was directed by Valérie Lépine, Christelle Millet-Fourrier – both are lecturers at the University of Grenoble-Alpes - and Fabienne Martin-Juchat - professor at the University of Grenoble-Alpes. All three are researchers in organizational communication.